Flavour from food to perception - Guichard, Elisabeth 1956-; Salles, Christian; Morzel,Martine; Le Bon,Anne-Marie (Chichester, UK John Wiley & sons, 2017)
"This book will cover all aspects of flavour perception, including aroma, taste and the role of the trigeminal nerve, from the general composition of food to the perception at the peri-receptor and central level. This book will answer to a growing need for multidisciplinary approaches to better understand the mechanisms involved in flavour perception"--Provided by publisher.
Keywords: Taste; Flavor; Chemical senses